Inventarisasi dan Analisis Jenis Tumbuhan Famili Liliaceae di Taman Inklusi, Kelurahan Citarum, Kota Bandung - Adinda Refa Shabira; Fathin Dhiya Amani; Ateng Supriatna (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The Liliaceae family has about 280 genera and about 4000 species that are widely distributed on earth. Based on their form of stature this family is a herbaceous group, which is generally geophytic, often poisonous, with rhizomes. All members of this family usually have layered tubers that produce steroidal saponins or steroidal alkaloids from phenylalanine or tyrosine. Inventory research was conducted at the Inclusion Park, Citarum Village, Bandung City. Inventory is an activity of grouping data on a plant species that occupies a certain area to collect data on species richness in an area. The method used in this research is the exploration method, by exploring along the research site and collecting information on the presence of plant species of the family. The results of the study obtained 3 species in the liliaceae family, namely Liriope spicata (Thunb.) Lour., Chlorophytum comosum, and Cordyline fruticosa (L.) A.Chev. Translated with DeepL.com (free version).